Beyond Happiness and Sadness: Affective Associations of Lyrics with Modality and Dynamics - Laura Tiemann; David Huron (Empirical Musicology Review, 2012)
A study is reported investigating the relationship between modality (major/minor) and dynamics (piano/forte) on four affects – as evident in the content of musical lyrics. Forty solo vocal works were sampled: 10 in the major mode with a loud (forte) dynamic level, 10 in the major mode with a quiet (piano) dynamic level, 10 in the minor mode with a loud dynamic level, and 10 in the minor mode with a quiet dynamic level. Sampled compositions were all tonal works from the Western vocal repertoire. Without hearing the music, 60 native-speakers of English, German, and French judged the language-appropriate lyrics according to four affects: sadness, happiness, passion, and tenderness. Results were consistent with predicted associations between minor-piano music and sadness, major-forte music and happiness, and minor- forte music and passion. A fourth predicted association between major-piano music and tenderness was skewed in the predicted direction, but was not statistically significant.